Cybercrime and Digital Society in Indonesia: Legal Challenges and Public Discourse - Kusnadi, Dedek; Efendi, Ghina Nabilah; Martins da Silva, Dulce (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2025)
Cybercrime is a communication technology offence that disrupts the public through the use of computers and the internet. It occurs due to the negative impact of technology affecting human life. Regarding legal protection, the government is obligated to protect every citizen from harmful actions, including cybercrime, which can cause both material and non-material harm to its users. Therefore, this study aimed to analyse cybercrime, which had become a global threat to both national and international security. Although cyber-related analysis had been widely conducted, studies focusing on the content analysis of cybercrime within the context of digital-era law remained limited. This study specifically examined the content of cybercrime discourse in Indonesia’s digital society. A descriptive qualitative method was adopted with data sourced from big data on social media, official reports, and journalistic materials related to the topic. Data analysis was carried out using the NVivo 12 Plus software and word processing applications for qualitative analysis. The results showed that cybercrime content on social media, particularly Twitter, was predominantly harmful, with 77.62% classified as moderately negative and 22.38% as very negative. The consistent use of the hashtag showed the widespread nature of cybercrime. Furthermore, the digital legal framework in Indonesia was found to be insufficient in addressing the complexities of cybercrime, rendering law enforcement weak and hampered by various structural and technical challenges.